29. Implementing stereotactic RapidArc treatments into clinical routine: From algorithm configuration to treatment validation. (December 2017) - Sergent, F.; Van Esch, A.; Basta, K.; Bertrand, P.; Corbice, C.; Fontaine, E.; Hambach, L.; Clermont, C.; Blavier, A.; Huyskens, D.
Abstract : Introduction: This work aims to aid the medical physicist with the safe implementation of RapidArc (RA) (Varian Medical Systems, Palo Alto, CA) stereotactic radiotherapy treatments (SRS/SBRT) into clinical routine, from treatment planning system (TPS) configuration to patient plan verification. Implementation procedures are applicable to different Varian linear accelerators, either equipped with a standard Millennium 120MLC or a high-definition HDMLC, but always with on-board imaging. Methods: A systematic approach was used to assure proper control of the different aspects of the implementation. First, an extensive series of detectors (all from PTW, Freiburg, Germany) – from numerous point dose detectors to the 1000SRS/Octavius4D 3D dose measurement system - were carefully benchmarked to assess their dosimetric characteristics, their precision and their practical usefulness. This benchmarking was performed independently of the TPS. Second, the necessary measurements were performed to include small field data in the Analytical Anisotropoic Algorithm (AAA) and Acuros (AXB) algorithm configuration. Third, validation of the Eclipse small field dose calculation was performed for both algorithms, starting off with static gantry (small) MLC fields and ending with RA SRS/SBRT test plans. Finally, pre-treatment QA procedures were implemented, executed and analyzed on all patient treatments. Results: While one can do a substantial part of the basic validation with a single, high resolution, directionally independent point dose detector, a water phantom and a small solid water phantom to hold this detector, a point dose measurement is insufficient to assess the geometric precision of the dose-fall off during arc delivery. Given the safety requirements for stereotactic treatments, it is therefore highly recommended to invest in a detector system that can provide 2D and 3D dose information as well. The 1000SRS was found to provide very reliable planar dose measurements and, in combination with the Octavius4D system, measurement-based 3D dose reconstructions. It is also the most efficient method, especially when multiple lesions are concerned. From the battery of validation measurements, it was found that, although the algorithm configuration as well as the MLC modeling within the Eclipse TPS could benefit from further improvements, the currently obtained results are within clinical acceptance for the specific requirements of stereotactic treatment plans. Conclusions: Target localization remains the key aspect of successful stereotactic radiotherapy and should be carefully addressed according to the treatment site. However, from a dosimetric point of view, when the appropriate measurement equipment is available, safe implementation of stereotactic RA treatments should be within reach of all radiotherapy departments outfitted with an up to date Clinac (or TrueBeam) and state-of-the-art on-board imaging.